1994
DOI: 10.1177/172460089400900203
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer-Associated Keratin 19 Fragments: Development and Biochemical Characterisation of the New Serum Assay Enzymun-Test® Cyfra 21–1

Abstract: From a panel of 4 murine monoclonal antibodies directed against keratin 19 various antibody combinations were evaluated in solid-phase enzyme-linked sandwich immunoassays for detection of soluble keratin 19 fragments in patient sera. One of these antibody combinations, comprised of the monoclonal antibodies Ks 19.1 and BM 19.21, was selected for further development to a routine test (Enzymun-Test CYFRA 21-1) because of its high diagnostic sensitivity and specificity for non-small cell lung carcinoma (NSCLC). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…Detection of this Asp396 neo-epitope by the M30 ELISA is, therefore, only possible following caspasedependent apoptosis. It has been postulated that necrosis of epithelial cells releases full-length cytokeratins into the extracellular space following breakdown of the cell membrane (Bodenmüller et al, 1994). In vitro studies have shown that induction of necrosis in a human breast epithelial cell line is associated with a significant increase in the concentration of extracellular CK18, as recorded by the M65 ELISA (Kramer et al, 2004).…”
Section: Histopathological Assessment Of Necrosis and Apoptosis In Rementioning
confidence: 99%
“…Detection of this Asp396 neo-epitope by the M30 ELISA is, therefore, only possible following caspasedependent apoptosis. It has been postulated that necrosis of epithelial cells releases full-length cytokeratins into the extracellular space following breakdown of the cell membrane (Bodenmüller et al, 1994). In vitro studies have shown that induction of necrosis in a human breast epithelial cell line is associated with a significant increase in the concentration of extracellular CK18, as recorded by the M65 ELISA (Kramer et al, 2004).…”
Section: Histopathological Assessment Of Necrosis and Apoptosis In Rementioning
confidence: 99%
“…Furthermore, a kit (CYFRA 21-1, Roche Diagnostics) is currently being marketed in some parts of Europe for specific detection of a lung cancer-associated K19 fragment (48,49). The assays used for these measurements have employed antibodies that recognize both the intact and the fragmented forms of K8, K18, and K19.…”
Section: Discussionmentioning
confidence: 99%
“…Selective antibodies raised against simple epithelium type cytokeratin, particularly the acidic (type I) subunit cytokeratin 19, have been shown to react with all histologies of lung cancers (Debus et al, 1984). A fragment of cytokeratin subunit 19 corresponding to epitope sequences lying within the sequences 311 -335 and 346 -367 (Bodenmüller et al, 1994) can be measured in serum by a sandwich assay, CYFRA 21-1, using two mouse monoclonal antibodies, KS 19-1 and BM 19 -21.…”
mentioning
confidence: 99%